익상편수술에서 결손부위의 크기에 맞게 양막을 재단하는 새로운 방법 - 이지영(Ji Young Lee); 황형빈(Hyung Bin Hwang) (Daihan angwa haghoi jabji, 2019)
목적: 익상편수술에서 결손부위의 크기에 맞게 양막을 재단하는 방법을 소개하고자 하였다. 증례요약: 익상편을 제거한 후 조직 결손부위 반대 방향을 주시하게 하고, 결손부위의 크기를 측정하여 양막을 실제 결손부위의 크기보다 1.5-2.0 mm 큰 사이즈로 잘라낸다. 결손 방향의 반대쪽으로 주시하고 있는 상태에서 결손 조직의 수직축부터 봉합하고, 눈이정위에서 미세하게 결손 방향 반대측으로 오게 한 후 수평축을 봉합한다. 여분의 양막 조직을 윤부의 윤곽에 맞게 절제하고, 이식된 양막에 고정 봉합을 추가한다. 결론: 양막은 신축성이 부족하고 찢어지기 쉬워 적당한 크기로 재단하는 것이 양막 이식의 성공률을 높이는 데 중요하다. 이 방법을 통해 양막을 정확한 크기로 견고하게 고정하여 이식할 수 있을 것으로 생각한다. Purpose: We introduce a new amniotic membrane (AM) for placement during pterygium surgery. Case summary: After excision of the pterygium, we measured the size of the defect with reference to the side opposite the defective area and prepared an AM with margins 1.5-2.0 mm greater than the defect size. The AM was first sutured vertically, with reference to the opposite side of the defect. Then we sutured the upper and lower horizontal axes, and positioned the eye, from the front, slightly away from the direction of the opposite side of the defect. The AM was cut by reference to its boundary at the limbus, and three fixation sutures were placed. Conclusions: Appropriate AM sizing is important in terms of AM transplantation; the AM is non-elastic and easily torn. Our technique transplants a correctly sized AM and anchors it firmly. KCI Citation Count: 0